Pengenalan Variasi Khat dalam Meningkatan Kemampuan Menulis Arab Siswa MIN Salatiga Melalui Ekstrakurikuler Kaligrafi - Yassirly Amrona Rosyada; Maidah, Siti Fatihatul; Fatimah Azzahro; Fina Idamatusilmi; Aisyah Khaq (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
The purpose of this study was to improve students' Arabic writing skills through a calligraphy media approach. This study uses the ABCD (Aset Based for Community Development) approach where the author actively assists activities through In Class Training (ICT) in calligraphy extracurricular activities every Saturday at MI Negeri Salatiga. There are 15 students participating in this calligraphy extracurricular activity, consisting of 7 female students and 8 male students. The results of this study indicate that holding calligraphy extracurricular activities at MIN Salatiga can improve students' accuracy, writing skills, and focus levels. These results were obtained based on observations, interviews, and documentation. Writing skills training is carried out by introducing variations of naskhi script to students. The introduction of this script is carried out since elementary school because it will be related to students' ability to express their imagination, thoughts and feelings through writing.